Estimating the level of knowledge, attitude and behavior towards environmental education among postgraduate students of Institute of Education, International Islamic University Malaysia: an exploratory analysis - Muhammadu Kijas, Abdul Cafoor; Masahina, Sarabdeen; Ibrahim, Mohd Burhan; Afroz, Rafia (2013)
Global climate change, regional air pollution, water pollution and solid waste might be some of the environmental problems caused by human behavior. Government and private environmental agencies implement techniques to reduce the environmental problems. However the human behaviors need to be changed for a sustainable development towards environment. Providing knowledge of to what extent the human behavior causes environmental problems and how does human contribute to serve the environment could be possible to change behavior. This study aimed to estimate the level of awareness, attitude and behavior of the students of Institute of Education of International Islamic University Malaysia towards environmental education. Theory of Responsible Environmental Behavior is being used. Underling factors were identified using Exploratory Factor Analysis and One-way ANOVA analysis was used to identify the affecting factors on environmental awareness, attitude and behavior of respondents. The results indicate that the level of knowledge regarding the environmental issues of the students is high. However, the attitude and behavior towards the environmental issues are poor. The results further reveal that there are no significant differences among students based on sex, the area grow up, age, and level of education towards environmental knowledge, attitude and behavior.